P60 Temporally close presentation of primary lung cancer and idiopathic pulmonary fibrosis (IPF): an analysis of incident IPF cases from 2007 – 2018. (12th November 2019) - Daniels, E; Kadwani, O; Molyneaux, P; George, P; Mann, J; Devaraj, A; Renzoni, E; Maher, TM; Kouranos, V; Kokosi, M; Kemp, S; Shah, P; et al.
Abstract : Background: Lung cancer is historically described as a late complication of IPF, implying that screening in early IPF would have a low yield. The frequency of finding lung cancer in newly diagnosed IPF is not known. Methods: The Lung Cancer multidisciplinary team (LCM) database at the Royal Brompton Hospital was retrospectively examined for the period 2007–18 to identify cases with underlying IPF. Additionally, new ILD referrals seen over the same period were retrospectively filtered for cases with a final/MDT diagnosis of IPF. Results: In the period of interest, 3267 cases of suspected lung cancer were referred by various parties to the LCM and a total of 1780 cases of IPF were diagnosed by the RBH ILD Unit. Of the latter, 61 were referred for exclusion of malignancy (mean age 70.7; 84% male; mean predicted FVC 80.1% and TLco 39.7%). Primary lung cancer was histologically confirmed in 30/61 (49.2%) cases and highly suspected in another 16 (26.2%) based on tumour behaviour and/or PET-FDG staging. The rate of cancer diagnosis amongst all IPF patients was therefore 2.6% (46/1780). Coexistent emphysema was present in exactly half (23/46) of this group. Cancer subtyping revealed 24 cases of non-small cell and 7 cases of small cell lung cancer. Patients considered unfit for biopsy had poorer lung function; FVC: 67.6%±21.9% vs. 84.9%±18.3% (P<0.05) and TLco: 32.3±13.1% vs. 42.6±10.5% (P<0.005). Lung cancer and IPF were diagnosed within 12 months of each other in 14/30 (46.7%) of those with confirmed malignancy; in five cases, radiological suspicion of cancer predated IPF diagnosis. The two entities were similarly identified within a 12-month interval in half of cases with a high-probability cancer that could not be biopsied. Overall, 1 in 2 cancers in the cohort was diagnosed at stages III/IV, a frequency lower than that for the general population (70–75%, CRUK 2014–15 data). Conclusions: Near-contemporaneous (<12-month interval) presentation of IPF and lung cancer is not rare in ostensibly 'mild' IPF especially when there is concomitant emphysema. A number of factors may account for the lower proportion of high-stage cancer in IPF patients including more frequent imaging prompted by symptom change.